Associations between young informal caring and mental health: a prospective observational study using augmented inverse probability weighting - King, Tania; Singh, Ankur; Disney, George (My University, 2021)
Background: Across the world, many young people are supplying unpaid, informal care. There is growing evidence of the impact of this caring role on the lives of young informal carers, however there has been little quantitative analysis of the mental health impacts. This research aimed to estimate the effect of informal caring at age 14/15 years on mental health at age 18/19 years. Method: Data was drawn from Waves 5, 6, 8 (2012-2018) of the Longitudinal Study of Australian Children. Effects of caring on mental health were assessed using augmented inverse probability weighting, with adjustment for potential confounders, and using the Kessler-10 measure of mental health. Caring was assessed with both a binary (any caring vs none), and a three category variable (no caring, less than daily caring, daily caring). Multiple imputation was carried out using chained equations, and analysis was conducted on both complete case (n=2165) and the imputed dataset (n=3341). Outcomes: In complete case models, any caring at age 14/15 years was associated with poorer mental health at age 18/19 years compared to those reporting no caring, with an average treatment effect (ATE) of 1.10 (95%CI 0.37, 1.83). The ATE of daily caring compared to no caring at age 14/15 years of age was 1.94 (95%CI 0.48, 3.39), and caring less than daily (compared to no caring) was associated with a treatment effect of 0.83(95%CI 0.06, 1.61). Associations were robust to several sensitivity analyses. Interpretation: These results suggest there is a mental health impact of caring in adolescence on mental health four years later. This highlights the need for support for young informal carers, particularly for those providing more intensive caring.
The Lancet Regional Health - Western Pacific
Keywords: Families and relationships; Health and wellbeing